Traditional Wisdom of Malay Community in Coal Songket Cloth in Padang Ginting Village, Talawi District, Coal District - Syafira, Adel Chia; Dora, Nulriza (AMK : Abdi Masyarakat UIKA, 2024)
This study explains the traditional wisdom of the Malay community in manufacturing and using Coal songket cloth in Padang Ginting Village, Talawi District, Batu Bara Regency. Songket Batu Bara is a cultural heritage with high historical and aesthetic value. The purpose of this study is to explore, traverse, and understand the practice of making songket cloth, as well as the important role of this fabric in the lives of local people. Research methods used include ethnography, interviews, and documentation. The study results revealed that the Malay community in Padang Ginting Village has inherited knowledge and expertise in making coal songket cloth for generations. The process of making this songket involves many stages that require high skill and accuracy. Apart from being a traditional dress, the coal songket also has social and cultural significance in traditional ceremonies and local celebrations. The results of this study provide insight into the traditional wisdom of the Malay community in preserving cultural heritage and unique handicraft arts. A deeper understanding of Coal songket can make a positive contribution to maintaining the sustainability of the traditions and cultural richness of the Malay community in the area.